Umuganda: The Ultimate Nation-Building Project? - Jaclyn Barnhart (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2011)
This research and presentation thereof considers the ritual umuganda in terms of its contribution to national identity. In doing so, I consider the history of the ritual, its transformation in purpose over time, and the accompanying sociological consequences of such purposes and transformations. The evidence in this case includes sociological analyses of the umuganda ritual itself; political speeches which underscore the type of popular mobilization contemporaneously undertaken and/or accomplished and its purpose for such; recent media articles relating to umuganda (written by both citizens and outsiders and by both those with affirmative and negative opinions concerning umuganda’s contribution to the Rwandan reconciliatory spirit and economy), as well as my own first-hand observation of and participation in umuganda. The available evidence demonstrates a strong correlation between participation in the ritual of umuganda and social and political mobilization in Rwanda’s earlier historical periods in which the state effectively delineated and managed a nation-building project. In conclusion, I argue that the effectiveness of the current umuganda ritual is largely unsuccessful in relation to nation-building, as it does not achieve a high degree of unified social or political mobilization within the Rwandan population that ultimately contributes to an identification with a single national identity.